PELAKSANAAN PERKAWINAN SEMARGA PADA MASYARAKAT BATAK MANDAILING DI TANAH RANTAU (STUDI DI DESA JANJI RAJA ROKAN HULU) - Yulia Wulandari; Zulherman Idris (JOURNAL EQUITABLE, 2023)
Marriage is carried out as a means to obtain offspring and expand kinship relations. Marriages that occur in indigenous peoples have their own characteristics or requirements, one of which is the prohibition of marriage with other members of the customary law community, as happened in the Mandailing Batak customary community. The problem in this research is what are the consequences of same-sex marriage for the Mandailing Batak people in overseas lands? This type of research is empirical research with primary data and supported by secondary data. The results of the study show that the Mandailing Indigenous people still adhere to their customs, especially from the aspect of marriage, even to overseas lands, even if marriages that conflict with customary law will still be subject to customary sanctions in the form of being disirang mangolu, ostracized or expelled from a village and not having a position in adat. in ancient times while in the present it is considered normal and is only required to pay a fine